Straightforward ladder sequencing of peptides using a Lys-N metalloendopeptidase. - Taouatas, N; Drugan, M; Heck, A; Mohammed, S (2008)
We introduce a method for sequencing peptides by mass spectrometry using a metalloendopeptidase that cleaves proteins at the amino side of lysine (Lys-N). When analyzed by electron transfer dissociation (ETD)-based mass spectrometric sequencing, Lys-N-digested peptides that contain a single lysine residue produce spectra dominated by c-type fragment ions, providing simple ladders for sequence determination. This method should be a valuable strategy for de novo sequencing and the analysis of post-translational modifications.